2022
DOI: 10.1002/jia2.25928
|View full text |Cite
|
Sign up to set email alerts
|

Food security reduces multiple HIV infection risks for high‐vulnerability adolescent mothers and non‐mothers in South Africa: a cross‐sectional study

Abstract: Introduction Adolescent girls and young women, including adolescent mothers, in Southern Africa have high HIV seroconversion and transmission. We need to know which risks drive HIV infections, and what can reduce these risks. Methods We interviewed 1712 adolescent girls and young women (11–23 years), including 1024 adolescent mothers who had conceived before age 20 and had a living child, from two health municipalities of South Africa's Eastern Cape Province between March 2018 and July 2019. Recruitment was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…[ 9 ] Another study in South Africa found that among nulliparous AGYW (aged 11–25), being food secure was protective against transactional sex. [ 23 ] Our study is unique in that it extends this literature with its focus on in-school AGYW in the understudied Rwandan context, as well as its focus on food security. Successful interventions addressing transactional sex include cash transfers, which address its upstream drivers, such as FI; [ 24 , 25 ] other behavioral interventions have not demonstrated impact.…”
Section: Discussionmentioning
confidence: 97%
“…[ 9 ] Another study in South Africa found that among nulliparous AGYW (aged 11–25), being food secure was protective against transactional sex. [ 23 ] Our study is unique in that it extends this literature with its focus on in-school AGYW in the understudied Rwandan context, as well as its focus on food security. Successful interventions addressing transactional sex include cash transfers, which address its upstream drivers, such as FI; [ 24 , 25 ] other behavioral interventions have not demonstrated impact.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research showed that, across 73 developing countries, increasing preschool enrolment to 50% in a single year could increase a countries' productivity by $33 billion across those children's lifetimes (Engle et al, 2011 ). Evidence‐based multi‐sectoral packages, which could include access to childcare, for pregnant adolescents and adolescent mothers are a crucial step in supporting their school progression and HIV risk reduction, strengthening positive future outlook and supporting the healthy development for the next generation (Cluver et al, 2022 ; Jochim et al, Forthcoming ). There are important future areas for research in understanding associations of different kinds of childcare settings with child and adolescent mother outcomes and differential impacts by age of children.…”
Section: Discussionmentioning
confidence: 99%
“…Designing focused interventions and public health strategies requires a thorough understanding of the prevalence of these risk factors. Studies have linked the experience of violence [ 11 ], lack of comprehensive sexual health education [ 12 ], and motherhood status [ 13 ] to multiple sexual risks among AGYW. However, there is a notable dearth of research concerning the relationship between lifetime pregnancy and multiple sexual risk behaviors among AGYW in South Africa.…”
Section: Introductionmentioning
confidence: 99%